Effects of cypermethrin on morphological, physiological and biochemical attributes of Cicer arietinum (Fabales: Fabaceae) - Siddiqui, Sazada (Frontiers in Sustainable Food Systems, 2024)
Cypermethrin, a synthetic pyrethroid, is a widely employed pesticide in large-scale commercial agriculture and domestic settings to control pests and boost crop yields. Despite its effectiveness in controlling pests, concerns persist about the potential ecological and human health impacts associated with its use. In the present study, the impact of cypermethrin on different parameters, including growth indices, pollen morphology and pollen fertility, chlorophyll and carotenoid content, hydrogen peroxide (H2O2) scavenging, lipid peroxidation (MDA concentration), superoxide dismutase (SOD), and catalase (CAT) activities, was investigated in Cicer arietinum L. The results showed that plants exhibited decreasing trends in plant height, number of branches, pods, and seeds per plant as cypermethrin concentrations increased. These changes resulted in significant reductions in the overall yield of the plants. The percentage of wrinkled pollen significantly increased with higher concentrations of cypermethrin and longer exposure durations. Exposure to cypermethrin showed significant variations in pollen fertility of C. arietinum at different concentrations and time intervals in comparison to control, which had a baseline pollen fertility of 79.12% ± 4.59. Chlorophyll and carotenoid content of C. arietinum were considerably affected by cypermethrin, indicative of potential disturbances in essential photosynthetic processes crucial for plant health. Further, with increasing concentrations of cypermethrin ranging from 100 mg/L to 500 mg/L, noticeable effects were observed on H2O2− scavenging, MDA concentration, SOD and CAT activities of C. arietinum in dose-dependent manner. Further, it was found that the duration of exposure and concentration of cypermethrin played a crucial role in exacerbating these detrimental effects. The findings of the present study raise concerns regarding the harmful effects of agricultural pesticides like cypermethrin and highlight the need for more research on the nutritional value of products derived from plants and seeds exposed to these agents.